2019
DOI: 10.1155/2019/8382160
|View full text |Cite|
|
Sign up to set email alerts
|

Comparability of Self-Ratings and Observer Ratings in Occupational Psychosocial Risk Assessments: Is There Agreement?

Abstract: Objective. The suitability of self-ratings and observer ratings within organisational management approaches is controversial. The aim of this study was to compare the degree of agreement between self-rated and observer-rated occupational psychosocial demands. The comparison took place within a work-activity and not worker-centred assessment, according to official policies for psychosocial risk assessment. Through simultaneous application of two versions of the same instrument, we aimed to reduce the rating bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The only exception is skill utilization (item 10), which does not relate to well-being, but positive strain-balance (data not shown). Nevertheless, we decided to keep this item in the practitioners' version of the questionnaire from the 2019th validation [12], as it seems to be a resource if present during task operation. One item that was removed from the practitioners' version was the question of a fixed place of work (item 16) because it delivered contradictory results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The only exception is skill utilization (item 10), which does not relate to well-being, but positive strain-balance (data not shown). Nevertheless, we decided to keep this item in the practitioners' version of the questionnaire from the 2019th validation [12], as it seems to be a resource if present during task operation. One item that was removed from the practitioners' version was the question of a fixed place of work (item 16) because it delivered contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should focus on validating the new instruments in relation to more objective work-related health outcomes. However, a previous study has shown that the subjective outcomes correspond to observer-ratings [12] and thus could be regarded as a rather "objective" assessment of the working conditions. Regarding objective health outcomes, physiological variables such as hair cortisol as a biomarker for chronic stress [38] or organizational outcome variables (e.g., sick leave days) could be considered.…”
Section: Main Conclusion From Both Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article titled “Comparability of Self-Ratings and Observer Ratings in Occupational Psychosocial Risk Assessments: Is There Agreement?” [ 1 ], References [5, 8] should be removed since they were recommended during the review process and do not contribute essentially to the topic.…”
mentioning
confidence: 99%